Workforce ageing in Public Administration: The influence of age-diversity climate on affective commitment and turnover intentions - Sousa, Inês; Ramos, Sara (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
An ageing workforce is one of the greatest challenges that organisations face today. With the postponement of retirement age to 66 years old and three months (Ordinance no. 67/2016) and the budgetary constraints for the recruitment of new workers, Public Administration is no exception. According to data from the Department of Statistics of Public Employment, in 2016, the average age of workers in Public Administration was 46.1 years old. Figures indicate that 33.7% of the 659 149 workers were aged between 45 and 54 years, and 23.6% were 55 or more years old. On behalf of organisational sustainability, Human Resources Management (HRM) in Public Administration will have to ensure that its workers will remain active, productive and motivated in the future. Previous research shows that workers’ needs change with age (e.g. Kooij, Jansen, Dikkers & De Lange, 2010). Hence, HRM has to develop organisational practices that meet the needs of people of all ages (Truxillo, Cadiz & Hammer, 2015; Walker, 1999) in order to create an age-diversity climate (Boehm, Kunze & Bruch, 2014). Age-diversity climate refers to the extent that workers perceive the nondiscriminatory treatment of workers of all age groups with regard to all relevant organisational practices, policies and procedures (Boehm et al., 2014). If workers believe they receive a nondiscriminatory age-related treatment, they will likely report an increasing level of emotional attachment to the organization, the so-called affective commitment. So, our first hypothesis proposes that age-diversity climate positively influences affective commitment. Also, workers who feel that are treated in an unfair and discriminatory manner will be more prone to leave the organisation. Therefore, our second hypothesis states that age-diversity climate negatively affects turnover intentions.